Paciente femenino de 55 años de edad con diabetes mellitus tipo 2 y obesidad grado 2. - León Sánchez, Cristina Mireya (2020)
The present study in a clinical case of a 55-year-old female housewife with 4 children domiciled in the city of Babahoyo, with a family history, father with liver Cáncer and mother with hypertension, surgical history 3 years ago underwent surgery laparoscopy of the gallbladder, allergy does not refer. He comes to the consultation due to the following symptoms: increased food intake, blurred vision, fatigue, dizziness and increased frequency of urination. Due to his clinical picture, complementary tests were carried out, which showed an elevation in his glycemia. Upon nutritional assessment according to her body mass index (BMI), the patient has grade II obesity, for which she is immediately referred to the nutritionist for timely intervention. The main objective of dietary treatment in this patient is to improve glucose levels and avoid complications in the patient through the nutrition care process. The patient will be given a nutritional treatment that will be appropriate according to the needs of the patient and control of her existing pathology. A follow-up and monitoring was carried out where it was possible to verify the improvement of the patient, a notable improvement in her biochemical data was observed, yielding results in normal values, in addition to a decrease in her BMI. Upon seeing the results of the nutritional treatment, the patient decides to continue with her treatment in order to avoid complications of her disease.